PENDIDIKAN AGAMA KRISTEN DAN DIGITAL PARENTING DI ERA 5.0 - Legi, Hendrik; Riwu, Maleachi; Legi, Devarsh Gevariel Dean Legi (Sekolah Tinggi Teologi Moriah, 2025)
The development of digital technology in the era of society 5.0 has had a major impact on the pattern of education and parenting of children, including in Christian families. This era demands the integration of artificial intelligence and human values, which poses a serious challenge in maintaining the faith, character, and morals of the younger generation. In the midst of increasingly complex technological trends, the role of Christian Religious Education (PAK) and digital parenting patterns are becoming increasingly important and inseparable. This study aims to examine how PAK can synergize with digital parenting to form a strong children's character in faith and digital wisdom. This research uses a qualitative approach with the literature study method (library research). Data was collected through analysis of theological sources, Christian education books, scientific articles, and documents related to parenting and technological developments in the 5.0 era. The analysis is carried out in a descriptive and theological hermeneutic manner to interpret the relevance of faith values in today's digital context. The theoretical basis of this research includes the principles of education in the family according to the Bible (Proverbs 22:6, Deuteronomy 6:6-9), the concept of digital parenting , and the understanding of society 5.0. The results of the study show that the integration between PAK and digital parenting can create a parenting pattern that not only protects children from the negative influence of technology, but also shapes them into spiritually resilient individuals, wise in using technology, and able to be bright in the digital world. Collaboration between families, churches, and schools is the key to delivering a relevant and transformative educational model in this digital era. Perkembangan teknologi digital dalam era masyarakat 5.0 membawa dampak besar terhadap pola pendidikan dan pengasuhan anak, termasuk dalam keluarga Kristen. Era ini menuntut integrasi antara kecerdasan buatan dan nilai-nilai kemanusiaan, yang menimbulkan tantangan serius dalam menjaga iman, karakter, dan moral generasi muda. Di tengah arus teknologi yang semakin kompleks, peran Pendidikan Agama Kristen (PAK) dan pola digital parenting menjadi semakin penting dan tidak terpisahkan. Penelitian ini bertujuan untuk mengkaji bagaimana PAK dapat bersinergi dengan digital parenting guna membentuk karakter anak yang kuat secara iman dan bijak secara digital . Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur (library research). Data dikumpulkan melalui analisis terhadap sumber-sumber teologis, buku pendidikan Kristen, artikel ilmiah, serta dokumen terkait parenting dan perkembangan teknologi era 5.0. Analisis dilakukan secara deskriptif dan hermeneutik teologis untuk menafsirkan relevansi nilai-nilai iman dalam konteks digital masa kini. Landasan teoritis penelitian ini mencakup prinsip-prinsip pendidikan dalam keluarga menurut Alkitab (Amsal 22:6, Ulangan 6:6-9), konsep digital parenting , serta pemahaman masyarakat 5.0. Hasil kajian menunjukkan bahwa integrasi antara PAK dan digital parenting dapat menciptakan pola pengasuhan yang tidak hanya melindungi anak dari pengaruh negatif teknologi, tetapi juga membentuk mereka menjadi pribadi yang tangguh secara spiritual, bijak dalam menggunakan teknologi, dan mampu menjadi terang di dunia digital . Kolaborasi antara keluarga, gereja, dan sekolah menjadi kunci utama dalam menghadirkan model pendidikan yang relevan dan transformatif di era digital ini.